Alkali metal cation adduct effect on polybutylene adipate oligomers: Ion mobility-mass spectrometry. (31st May 2019) - Crescentini, Tiffany M.; May, Jody C.; McLean, John A.; Hercules, David M.
Abstract: Polyurethane (PU) di-block copolymers are one of the most versatile polymeric materials, comprised of hard and soft segments that contribute to PU's broad range of applications. Polybutylene adipate (PBA) is a commonly used soft segment in PU systems. Characterizing the structure of PBA polymers is essential to understanding complex heterogeneity within a PU sample. In this study, ion mobility-mass spectrometry (IM-MS) and tandem mass spectrometry (MS/MS) are used to structurally characterize a PBA standard (Mn = 2250) adducted with a combination of monovalent alkali cations (Li, Na, K, Rb, and Cs). IM-MS profiles show unique trends associated with each cation-adducted PBA sample. Charge state trends: +1, +2, and +3 were extracted for cation-adducted PBA oligomers, and investigated to study gas-phase transitional folding. To quantitatively assess the gas-phase structural similarities and differences, a statistical test (ANOVA) was used to compare PBA oligomer-cation collisional cross sections (CCS). Fragmentation studies (MS/MS) identified the unique behavior of Li and Na for promoting 1, 5 H-shift and 1, 3 H-shift fragmentation, whereas the PBA precursor preferentially loses the larger K, Rb, and Cs cations as the ion activation energy is increased. The combination of adducted alkali cations, IM-MS, and MS/MS allow for unique structural characterization of this important PBA system. Graphical abstract: Image 1 Highlights: Monovalent alkali cations (Li, Na, K, Rb, and Cs) were used to structurally characterize PBA oligomers. Characterization via IM-MS, IM-MS/MS, and ANOVA. Unique charge state trends (z = +1, +2, and +3) were extracted for cation-adducted PBA oligomers. Unique fragment ions were observed for Li and Na, while the larger cations (K, Rb, and Cs) only showed cation loss.